Conflitos linguísticos no jornalismo brasileiro : análise à luz das políticas linguísticas - Santos, Caroline Lima dos (2024)
Human contact, since the origin of humanity, is reported from the occurrence of conflicts that extend to linguistic contact between two or more languages in the same territory. Initially, linguistic diversity was considered by the field of language policy as a problem for new nations that needed to be resolved after the end of the Second World War. In the face of political scenarios, languages and speakers were minimized, just as certain languages reached the tip of the hierarchical pyramid of languages, being called official languages, symbols of a state and a single people. From this perspective, the emergence of linguistic conflicts and repressions is intensified, this phenomenon being the basis of the work in question. In this way, the main objective of this study is to map in the Brazilian journalistic media and typify linguistic conflicts based on the hypotheses that the country does not have an ideal development in linguistic politics and law, as well as that linguistic divergences indicate the denial of the character multilingual and plurilingual in Brazilian territory. The theoretical basis is arranged in two main axes, the first of which intends to develop the discussion on Linguistic Policy and Law, as a field of knowledge, through the concepts of Abreu (2016, 2018, 2020), Calvet (2021), Jonhson and Ricento (2013), Lagares (2018), Mariani (2004), Severo (2013, 2022), Sigales-Gonçalves (2020, 2022), Spolsky (2009, 2012) and Rodrigues (2022). Continuing the debate on conflicts in a macro and micro form, through contributions from sociology, anthropology, and linguistics, with the help of Cardoso de Oliveira (2008), Giddes and Sutton (2016), Jacquemet (2000), Lemos (2021) and Montanari ( 2013), Darquennes (2015) and Watts (2015) on the state of the art of linguistic conflict and its relationship with contact linguistics and Dubinsky and Davies (2018), McRae (1983), Nelde (1996) and Ninyoles (1989) in the categorization of conflicts. The methodological procedures of the investigation, supported by Godoy (1995), on qualitative-documentary research, delimit the steps of the research into three phases, which correspond to: the search for journalistic media on news sites that expose situations of linguistic conflicts, followed by content analysis and categorization of the observed conflict, through checking which political actions provoked the confrontation, such as the treatment of data analyzed based on the categories: participants, domain, relationship between the individual and the group, the purpose and object of the conflict and the typologies of linguistic conflicts. The results indicate confirmation of the initial hypotheses, and that the occurrence of conflicts is directly related to the denial of linguistic rights.